Liberalizm i męstwo bycia. Pytania o niepewność = Liberalism and heroism of existence. Questions about uncertainty - Frąckowiak, Tadeusz; Frąckowiak, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
The dissertation deals with the problem of global changes and contemporary ideas such as democracy, liberalism, postmodernism as well as with the place of an individual and education in these contexts.
Keywords: liberalizm; demokracja; postmodernizm; edukacja